2020
DOI: 10.1021/acs.macromol.0c00067
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Cohesive Interaction in Mechanical Behavior of a Glassy Polymer

Abstract: Understanding the mechanical behavior of glassy polymers at a fundamental molecular level is of critical importance in engineering and technological applications. Among various molecular parameters, cohesive interactions between polymer chains are found to play a key role in influencing the thermomechanical response of glass-forming polymers. Here, we employ atomistically informed coarse-grained molecular dynamics (CG-MD) simulations to study the mechanical properties of the polymer material in a glassy state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 87 publications
(156 reference statements)
3
39
0
Order By: Relevance
“…In summary, it can be seen in Figure that while the fitted T 0 is insensitive to the fitting procedure and evidently increases with increasing α, we cannot obtain a reliable trend for D . A recent paper, which focuses on the influence of cohesive interaction strength on the mechanical properties of polymers, has indicated that the fragility given by 1/ D increases with increasing cohesive interaction strength, a finding in conflict with the predictions from the GET. However, the range of τ α considered in ref is quite limited and also varies systematically for each cohesive energy parameter, so the VFT fits are expected to have the same issues, as discussed above.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In summary, it can be seen in Figure that while the fitted T 0 is insensitive to the fitting procedure and evidently increases with increasing α, we cannot obtain a reliable trend for D . A recent paper, which focuses on the influence of cohesive interaction strength on the mechanical properties of polymers, has indicated that the fragility given by 1/ D increases with increasing cohesive interaction strength, a finding in conflict with the predictions from the GET. However, the range of τ α considered in ref is quite limited and also varies systematically for each cohesive energy parameter, so the VFT fits are expected to have the same issues, as discussed above.…”
Section: Resultsmentioning
confidence: 95%
“…Bending constraints are imposed by an angle potential having the following form proposed by Hsu and Kremer where the bond angle is given by θ = cos –1 [( b j · b j + 1 )/(| b j ∥ b j + 1 |)] in terms of the bond vector b j = r j – r j – 1 between two neighboring beads j and j – 1. Based on previous work, where we have systematically investigated the influence of the chain stiffness parameter a θ on polymer glass formation at a fixed value of b θ = 1.5, the present work selects the parameters a θ = 6ε and b θ = 1.5 to represent polymer melts with bending constraints, while polymer melts without bending constraints are modeled naturally using a θ = 0ε, i.e., without the angle potential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt b θ = 1.5 based on our previous work. 85 Nonbonded pair interactions are described by a truncated-and-shifted LJ potential,…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Nanosized fillers are commonly added to polymer matrices to impart desirable properties such as conductivity and mechanical strength. However, the enhancement of such properties depends on a complex interplay of the nanoparticle–polymer and nanoparticle–nanoparticle interactions and the total surface area of nanoparticles exposed to the polymer matrix. The exposed surface area, in turn, critically depends on the degree of dispersion of the nanofillers in the polymer host. As nanoparticle–polymer attractive interactions generally suppress chain relaxation dynamics and repulsive or nonattractive interactions enhance them; increasing the nanoparticle–polymer attraction would be expected to reduce bulk free volume, V f , and increase the glass-transition temperature, T g .…”
Section: Introductionmentioning
confidence: 99%